Evaluation of Teaching by Teleconference: Leadership Development in Nursing Organization Course Case Study - นันท์ศุภวัฒน์, อภิรดี; สกุลพรรณ์, สมบัติ; ศรีธีระจิตต์, กริช; จินดาธรรม, อานนท์; สุโอชมา, ไพชยันต์ (Journal of The Royal Thai Army Nurses, 2018)
This study was to evaluate a teaching by teleconference case study from the Leadership Development in nursing organization course. The study sample included, the course instructor, and a nursing administrator. The data were collected using the Evaluation of Teaching by Teleconference questionnaire. Data were analyzed by using descriptive analysis with frequency and percentage, and content analysis. Research findings revealed that: 1. The students and instructor agreed that teleconference teaching increased learner outcomes, teaching methodology, and utilization. 2. The students, instructor, and nursing administrator thought that teleconference teaching saved expenses and travel time in that no travel is required for both students and instructors as well as expanded upon opportunities. 3. Barriers and obstacles: The students, instructor, and nursing administrator commented that resources such as equipment, classroom, and staff are barriers of teleconference teaching difficult. In conclusion, teleconference teaching can positively support learner outcomes, teaching methodology, and utilization. Instructors and administrators should apply teleconference teaching to other courses but well-prepared instruments, classrooms, and staff are needed